2020
DOI: 10.4067/s0718-221x2020005000311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of factors on direct screw withdrawal resistance in medium density fiberboard and particleboard

Abstract: The effect of chipboard screw sizes on screw withdrawal strength was investigated using different screw insertion technique. Large diameter chipboard screw has a thicker screw thread depth than small size chipboard screw. If large chipboard screw tested on screw withdrawal test, then it will have significantly higher screw withdrawal strength than smaller chipboard screw because it will have better particle grip during screw insertion. The objective of this study is to determine screw withdrawal strength of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…They concluded that the screw withdrawal resistance value is linearly proportional with screw diameter. Similar conculsions was obtained by Yorur et al (2020). Regardells to type of material they have used (MDF and particle borards) they shoved that ratio between root of screws and predilled hole has significant influence on screw withdrawal strength.…”
Section: Influence Of Diametar Of Drilled Holesupporting
confidence: 75%
See 1 more Smart Citation
“…They concluded that the screw withdrawal resistance value is linearly proportional with screw diameter. Similar conculsions was obtained by Yorur et al (2020). Regardells to type of material they have used (MDF and particle borards) they shoved that ratio between root of screws and predilled hole has significant influence on screw withdrawal strength.…”
Section: Influence Of Diametar Of Drilled Holesupporting
confidence: 75%
“…According to obtained results, they concluded that beech wood had highest values of screw withdrawal resistance among five tree species, and that mositure content effects withdrawal resistance. Yorur et al (2020) analyse direct screw withdrawal force from various types od wood based panels. Among other things, they concluded that existance of pilot hole has significant influence on withdrawal strength.…”
Section: Introductionmentioning
confidence: 99%
“…Because as Tor et al (2016) reported, the structural unity of a product is directly correlated to the connection ability or performance of the members. And, SHR is one of the performance indicators that is adversely affected by soaking to water (Yorur et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Wood fibers between 121,07-125,42 kp. Yorur et al (2020) have explained that the highest direct screw withdrawal resistance the test blocks with polyurethane and the lowest direct screw withdrawal resistance the test blocks without a pilot hole drilled in both materials. According to the results, medium density fiberboard was best measured direct screw withdrawal resistance than particleboards.…”
Section: The Results Of the Surface Screw Holding Ability Test (N)mentioning
confidence: 99%